Strategi Kemandirian Pesantren Melalui Peningkatan Kualitas Manajemen di Pesantren Bahrul Ulum Sungailiat Bangka - Selamet Raharjo (AL-Ikhtiar : Jurnal Studi Islam, 2025)
The initial step to improving the quality of education and the independence of Islamic boarding schools is to implement an educational system that aligns with the characteristics of the Islamic boarding school and strengthen its management. The success of an Islamic boarding school is largely determined by effective management, encompassing efficient planning, organization, direction, and supervision. This study aims to describe the strategy of Islamic boarding school independence in improving management at Bahrul Ulum Islamic Boarding School, Sungailiat, Bangka, and to analyze the supporting and inhibiting factors. The method used is descriptive qualitative, with data collection through observation, interviews, and documentation. Data analysis was conducted through the stages of reduction, presentation, and conclusion drawing. The results indicate that the strategy for Islamic boarding school independence at Bahrul Ulum is implemented through improving the quality of management based on managerial functions. At the planning stage, the Islamic boarding school has a clear and directed program strategy. The organizing stage is well-functioning, with a proportional division of tasks and responsibilities between the administrators and the asatidz (teacher). The directing stage is carried out intensively with direct guidance from the leadership in every Islamic boarding school activity. The monitoring stage is carried out through a system of evaluation and continuous improvement by the responsible team. By implementing these four management functions, Bahrul Ulum Islamic Boarding School has succeeded in strengthening its institutional independence and increasing the effectiveness of its governance. Langkah awal untuk meningkatkan kualitas pendidikan dan kemandirian pondok pesantren ialah menanamkan sistem pendidikan yang sesuai dengan karakter pesantren dan memperkuat kualitas manajemennya. Keberhasilan suatu pesantren sangat ditentukan oleh manajemen yang efektif, meliputi perencanaan, pengorganisasian, pengarahan, dan pengawasan yang dijalankan secara efisien. Penelitian ini bertujuan mendeskripsikan strategi kemandirian pesantren dalam meningkatkan manajemen di Pondok Pesantren Bahrul Ulum Sungailiat Bangka serta menganalisis faktor pendukung dan penghambatnya. Metode yang digunakan adalah deskriptif kualitatif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Analisis data dilakukan melalui tahapan reduksi, penyajian, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa strategi kemandirian pesantren di Bahrul Ulum dilakukan melalui peningkatan kualitas manajemen berbasis fungsi-fungsi manajerial. Pada tahap perencanaan, pesantren telah memiliki strategi program yang jelas dan terarah. Tahap pengorganisasian berjalan baik melalui pembagian tugas dan tanggung jawab yang proporsional antar pengurus dan asatidz. Tahap pengarahan dilaksanakan secara intensif dengan bimbingan langsung dari pimpinan dalam setiap kegiatan pesantren. Sedangkan tahap pengawasan dilakukan melalui sistem evaluasi dan perbaikan berkelanjutan oleh tim penanggung jawab. Dengan penerapan empat fungsi manajemen tersebut, pesantren Bahrul Ulum berhasil memperkuat kemandirian kelembagaan dan meningkatkan efektivitas tata kelolanya.